Pengaruh Fashion Involvement Dan Hedonic Shopping Value Terhadap Impulse Buying Pada Matahari Depertment Store Di Mall Lembuswana Samarinda - Iis Marlina (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
ABSTRACTThis study aims to determine the effect Influence Fashion Involvement and Hedonic Shopping Value Against Impulse Buying In The Sun Depertement Store In Samarinda by using multiple regression analysis. Results showed variable Fashion Involvement and Hedonic Shopping Value simultaneously positive and significant impact on the Sun Depertement Buying In Store In Samarinda. The R value of 0.595 means that there is a relationship which was of variable Fashion Involvement and Hedonic Shopping Value on Impulse Buying. The coefficient of determination (R2) of 35.40 per cent it shows the proportion of variable contribution Fashion Involvement and Hedonic Shopping Value to fluctuations Impulse Buying. From t test results (Partial) shows variable Fashion Involvement and Hedonic Shopping Value has tcount ttable, it indicates that the variable Fashion Involvement and Hedonic Shopping Value positive and significant impact on impulse buying, thus receiving the first and second hypothesis. Partial test results showed that the variables fashion involvement dominant influence on impulse buying. Keywords: Fashion Involvement, Hedonic Shopping Value, Impulse Buying